2002
DOI: 10.1046/j.1432-1033.2002.03311.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural diversity and transcription of class III peroxidases from Arabidopsis thaliana

Abstract: Understanding peroxidase function in plants is complicated by the lack of substrate specificity, the high number of genes, their diversity in structure and our limited knowledge of peroxidase gene transcription and translation. In the present study we sequenced expressed sequence tags (ESTs) encoding novel heme-containing class III peroxidases from Arabidopsis thaliana and annotated 73 full-length genes identified in the genome. In total, transcripts of 58 of these genes have now been observed. The expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
253
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(268 citation statements)
references
References 59 publications
11
253
0
4
Order By: Relevance
“…The homology between paralogs in a plant ranges from 30% to 100%, but very close orthologs exist, even between evolutionarily distant plants. All plant peroxidases contain invariant amino acids essential for their catalytic properties and for their proper folding (Welinder et al, 2002 proteins, like peroxidases from prokaryotes, fungi. The key amino acids that interact with heme are also found in hemoglobins and cytochromes.…”
Section: Introductionmentioning
confidence: 99%
“…The homology between paralogs in a plant ranges from 30% to 100%, but very close orthologs exist, even between evolutionarily distant plants. All plant peroxidases contain invariant amino acids essential for their catalytic properties and for their proper folding (Welinder et al, 2002 proteins, like peroxidases from prokaryotes, fungi. The key amino acids that interact with heme are also found in hemoglobins and cytochromes.…”
Section: Introductionmentioning
confidence: 99%
“…2). In fact, it is known that protein structure, amino acid residues and protein size are conserved in all class III peroxidases [5,35]. CavPrx showed a "three intron" structure that is a common feature of the most of class III peroxidases in rice and Arabidopsis [2,7].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first class III peroxidase isolated in C. avellana and Real Time analysis showed that it is expressed in the styles, with a peak of expression in mature styles; in addition its level of expression increased significantly in styles pollinated with compatible pollen. Despite most of plant peroxidases are active in all part of the plant [5,7] some example of localized peroxidases in particular tissue/organ exist in literature, as reported in the introduction. In particular, five peroxidases were identified to be expressed in particular parts of the flower: GhPrx37 in G. hirsutum resulted expressed only in stamen and pollen [12]; SsqPrx01 in S. squalidus was demonstrated to be localized in the stigmatic papillae and expressed only in stigmas with maximal level at anthesis [6]; AtPrx28, AtPrx39 and AtPrx58 in A. thaliana resulted expressed in stigmas [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations